An Analysis Of Income And Efficiency Of Robusta Coffee Farming In Lubuk Saung Village, Sebrang Musi Sub-District Kepahiang Regency - Meilinda Dwi Anjarwati; Ana Nurmalia; Herri Fariadi (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the income and efficiency of robusta coffee farming conducted by farmers in Lubuk Saung Village, Seberang Musi District, Kepahiang Regency. Methodology: The research was conducted in May 2024 using a quantitative descriptive method. The sample size was determined using the Slovin formula from a total population of 69 robusta coffee farmers. Results: The average robusta coffee production per hectare per year is 463 kg, generating a total revenue of IDR 27,786,086 annually. Average production costs are IDR 2,379,405.80, resulting in a net income of IDR 25,406,682 per hectare per year. Findings: The R/C ratio of 1.18 indicates that every IDR 1 spent generates IDR 1.18 in revenue. Originality: This research highlights the economic feasibility of robusta coffee farming. Novelty: It provides detailed financial analysis for local farming practices. Conclusion: Robusta coffee farming in Lubuk Saung is profitable and efficient. Type of Paper: Empirical research.